Synthesis and Optical Characterization of Mixed Ligands Beryllium Complexes for Display Device Applications - Vandna Nishal; Devender Singh; Raman Kumar Saini; Vijeta Tanwar; Shri Bhagwan; Sonika Kadyan; Ishwar Singh; Pratap Singh Kadyan (International Journal of Optics)
Synthesis and photoluminescent behaviour of mixed ligand based beryllium complexes with 2-(2-hydroxyphenyl)benzoxazole (HPB) and 5-chloro-8-hydroxyquinoline (Clq) or 5,7-dichloro-8-hydroxyquinoline (Cl2q) or 2-methyl-8-hydroxyquinoline (Meq) or 8-hydroxyquinoline (q) are reported in this work. These complexes, that is, [BeHPB(Clq)], [BeHPB(Cl2q)], [BeHPB(Meq)], and [BeHPB(q)], were prepared and their structures were confirmed by elemental analysis, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and thermal analysis. The beryllium complexes exhibited good thermal stability up to ~300°C temperature. The photophysical properties of beryllium complexes were studied using ultraviolet-visible absorption and photoluminescence emission spectroscopy. The complexes showed absorption peaks due to π-π∗ and n-π∗ electronic transitions. The complexes emitted greenish blue light with peak wavelength at 496 nm, 510 nm, 490 nm, and 505 nm, respectively, consisting of high intensity. Color tuning was observed with changing the substituents in quinoline ring ligand in metal complexes. The emitted light had Commission Internationale d’Eclairage color coordinates values at x=0.15 and y=0.43 for [BeHPB(Clq)], x=0.21 and y=0.56 for [BeHPB(Cl2q)], x=0.14 and y=0.38 for [BeHPB(Meq)], x=0.17 and y=0.41 for [BeHPB(q)]. Theoretical calculations using DFT/B3LYP/6-31G(d,p) method were performed to reveal the three-dimensional geometries and the frontier molecular orbital energy levels of these synthesized metal complexes.